Classification of Strategies for Dealing with Student Relativism and the Epistemic Conceptual Change Strategy. - Pfister, J.
Student relativism is a widespread phenomenon in introductory philosophy courses. It is a pressing issue for teachers because it seems to undermine the very purpose of philosophy. Since the 1980s there is a debate about how to understand and how to deal with student relativism. However, there is as yet no comprehensive presentation of the debate. The first aim of the article is to offer a classification of the strategies for dealing with student relativism and a presentation and short assessment of the main strategies from the debate. The second aim is to present a new strategy based on the theory of conceptual change and drawing on the results from empirical research in developmental psychology on epistemic cognition. I call it the epistemic conceptual change strategy.